Rumah Rehat Tanah Rata, 39000, Tanah Rata, Cameron Highlands, Pahang - Mohd. Faizal Rahmat @ Mamat; Mohd. Rosli Hassan; Fithri Mustafa; Mohd. Azhan Musa; Nor Alina Azmi; Lim Ei-Leen (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Measured Drawing (Jabatan Senibina)) - Universiti Teknologi Malaysia, 2002